Advances in heterocyclic chemistry. - Katritzky, Alan R. (Advances in heterocyclic chemistry, 2007)
Established in 1960, Advances in Heterocyclic Chemistry is the definitive serial in the area-one of great importance to organic chemists, polymer chemists, and many biological scientists. Written by established authorities in the field, the comprehensive reviews combine descriptive chemistry and mechanistic insight and yield an understanding of how the chemistry drives the properties. * Up-to-date results in the subject which continues to gain importance and expand * Makes available to graduate students and research workers in academic and industrial laboratories the latest reviews on wide variety of heterocyclic topics * The series forms a very substantial database covering wide areas of heterocyclic chemistry.